2013
DOI: 10.1007/s11695-013-1160-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Weight in Comparative Studies of Bariatric Surgery vs Conventional Medical Therapy: A Systematic Review and Meta-Analysis

Abstract: We performed a meta-analysis of weight loss and remission of type 2 diabetes mellitus (T2DM) evaluated in randomized controlled trials (RCTs) and observational studies of bariatric surgery vs conventional medical therapy. English articles published through June 10, 2013 that compared bariatric surgery with conventional therapy and included T2DM endpoints with ≥12-month follow-up were systematically reviewed. Body mass index (BMI, in kilogram per square meter), glycated hemoglobin (HbA1C, in degree), and fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(143 citation statements)
references
References 77 publications
6
126
0
11
Order By: Relevance
“…About one-third of all participants who received bariatric surgery were diabetic, indicating positive selection of diabetes patients for this intervention, consistent with current policy recommendations that bariatric surgery should be utilised in the management of obesity-associated comorbidity. Changes in mean HbA 1c in our study were similar to those reported in previous studies, 72 but rates of diabetes remission after surgery reported in the present study were generally lower than those noted in published reviews, which ranged from 59% to 92%. 6,32,70 However, case definitions have varied.…”
Section: Summary Of Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…About one-third of all participants who received bariatric surgery were diabetic, indicating positive selection of diabetes patients for this intervention, consistent with current policy recommendations that bariatric surgery should be utilised in the management of obesity-associated comorbidity. Changes in mean HbA 1c in our study were similar to those reported in previous studies, 72 but rates of diabetes remission after surgery reported in the present study were generally lower than those noted in published reviews, which ranged from 59% to 92%. 6,32,70 However, case definitions have varied.…”
Section: Summary Of Findingssupporting
confidence: 88%
“…One incorporated RCTs and controlled cohorts both separately and together into random-effect meta-analyses. 72 Combining the 11 observational studies and five RCTs together gave a pooled OR of 9.8 (95% CI 6.1 to 15.9). The other used narrative analysis to discuss the results of five RCTs, four of which matched the former review.…”
Section: Type 2 Diabetes Remissionmentioning
confidence: 99%
“…The diabetic patients with BMI > 35 kg/m 2 are currently eligible for bariatric surgery, according to the NIH Consensus Criteria for bariatric surgery. Recent meta-analyses of 16 studies with 6131 patients and mean 17.3-month follow-up have found bariatric surgery to be superior to conventional medical therapy in achieving significant weight loss, HbA1c and fasting plasma glucose reduction and diabetes remission [51]. Thus, bariatric surgery has been accepted as the most effective treatment along with significant metabolic benefits for patients with T2DM and BMI > 35 kg/ m 2 [52].…”
Section: Alpha-glucosidase Inhibitors (Agis)mentioning
confidence: 99%
“…Bariatric surgery has emerged as the first (and, so far, only) technology associated with significant success against severe obesity [29][30][31] and its associated comorbidities [32] for a large proportion of treated patients. The procedure has demonstrated significant cost savings and return on investment for patients with class 3 obesity (i.e., BMI C40.0 patients) [33][34][35][36][37][38][39][40][41] and may be of benefit for other categories of patients [19].…”
Section: Three Recent Trends Suggest That Obesity and Its Challenges mentioning
confidence: 99%